1989
DOI: 10.3758/bf03209806
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental responding by rats on free-operant schedules with components that schedule response-dependent reinforcer omission: Implications for optimization theories

Abstract: In two experiments, we assessed whether rats optimize the number of reinforcers per response. In Experiment 1, one group of rats was trained to leverpress for food reinforcement on a simple variable-interval (VI) 60-sec schedule. For another group, a negative fixed-ratio component was imposed on the VI schedule to produce a conjoint contingency in which reinforcement became available on the VI schedule but was omitted when the ratio criterion was satisfied. In Experiment 2, one group of rats responded on a VI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…For example, Peele et al (1984) noted that the rates of response on VI and VR schedules became more similar to one another when the length of the reinforced IRT on these schedules was equated through a yoking procedure. Additionally, evidence from the study of many different contingencies has shown that organisms' responding can be maintained by contiguous response-reinforcer pairings, even when this leads to a reduction in the overall rate at which reinforcement is obtained (see Reed & Schachtman, 1989;Vaughan & Miller, 1984). Such evidence suggests that organisms are not particularly sensitive to the overall rela-tion between responding and reinforcement, but rather they are more sensitive to local response-reinforcer pairings.…”
mentioning
confidence: 99%
“…For example, Peele et al (1984) noted that the rates of response on VI and VR schedules became more similar to one another when the length of the reinforced IRT on these schedules was equated through a yoking procedure. Additionally, evidence from the study of many different contingencies has shown that organisms' responding can be maintained by contiguous response-reinforcer pairings, even when this leads to a reduction in the overall rate at which reinforcement is obtained (see Reed & Schachtman, 1989;Vaughan & Miller, 1984). Such evidence suggests that organisms are not particularly sensitive to the overall rela-tion between responding and reinforcement, but rather they are more sensitive to local response-reinforcer pairings.…”
mentioning
confidence: 99%
“…This means that the molecular or local aspects of the schedule could also account for the lower response rates on VI schedules. Vaughan and Miller (1984) suggest that such confounds between the molecular and molar aspects of the contingencies make the use of simple schedules problematic, and that on more complex schedules, there is very little support for a molar view (see also Reed & Schachtman, 1989).The variable-interval-plus-linear-feedback (VI ) schedule (McDowell & Wixted, 1986) is an important schedule to study in the investigation of molar sensitivity. …”
mentioning
confidence: 99%
“…One issue of interest is why rats in the present experiment tended to respond at the vertex of the feedback function whereas subjects in experiments on negative slope schedules respond at rates much higher than the vertex of the feedback function (Jacobs & Hackenberg, 2000;Reed & Schachtman, 1989, 1991Vaughan & Miller, 1984). One possibility is the difference in the vertex of the feedback function in the present experiment and in negative slope schedule experiments.…”
Section: Discussionmentioning
confidence: 66%
“…Baum concluded that this cost-benefit optimization account provided a better description of single-schedule variable-interval (VI) and variable-ratio (VR) performance than did the matching law (Herrnstein, 1970). More recent results from negative slope schedules, howev-er, have been taken as strong evidence against optimization accounts of single-schedule performance (Jacobs & Hackenberg, 2000;Reed & Schachtman, 1989, 1991Vaughan & Miller, 1984). On negative slope schedules, pigeons (Vaughan & Miller, 1984), rats (Reed & Schachtman, 1989, 1991, and humans (Jacobs & Hackenberg, 2000) typically respond at rates higher than necessary to maximize reinforcer rate, a finding inconsistent with optimization accounts that predict maximization of overall reinforcer rate.…”
Section: ____________________________________________________________mentioning
confidence: 99%